THE CORRELATION BETWEEN VENTILATION SPACE, HUMIDITY, SUNLIGHTING, DENSITY OF OCCUPANTS, AND NUTRITIONAL STATUS WITH ACUTE RESPIRATORY INFECTION SUFFERED BY CHILDREN ONE TO FIVE YEARS OLD AT MOJOSONGO VILLAGE, SURAKARTA CITY IN 2005. - Margo Utomo; F. Tri Hastuti (JURNAL LITBANG, 2007)
Bockground:There were 72,27 % of acute respiratory infection cases in Sibela Public Health Center, Kalurahan Mojosongo in 2004. In addition, there were 49 % houses at the end of December 2004 which were not qualified for living, there were: not enough ventilation space, few sunlighting coming in the house, too density of occupant, and lack of nutrition for children one to five years old.Purpose : to find out the correlation between ventilation, huntidity, sunlighting, density of occupants, and rutritional stahrs and acute respiratory infection suffered by children oneto.five years old in Mojosongo village, Surakarta City..Method : The study uses eksplanatory research by surveying method, interviewing by giving questionairs, observation and measttring by case control design.The population are 66 babies at 12 to 59 months old who came in Sibela Public Health Centt"e surakarta fi'om mid April to May 2005. The sample is 33 babies suffired from acute respiratory infection as the case group and 3i babies not suffered from acute respiratory infection as the control group by using quota sampling technique. Independent variable were ventilation, humidity, sunlighting, density of occupants, and nutritional status of children one to five years old. Dependent variable was acute respiratory tract infection.To analyze the risk of each variable, the shtdy uses ODDS Ratio. Chi Square test was used to/ind out the correlation of the variables.Result : Descriptive analisis shows that the biggest percentage is 100 % for humidity, 93,9 %for good ruttritional status, 59,1 %for high density of occupants and, si.,0 % for good house ventilation space and sunlighting..with chi square test p : 0,012 for ventilation space, constant for humidity, p : 0,000 for sunlighting, p : 0,0a9 for density of occupants, and p : 0,748 for nutritional status of children one to five years old.Through ODDS Ratio analysis, the writers finds out that unqualified ventilation had 7,233 times; highly density of occupants had 4,342 times and sunlighting had 1g,254times risk for children one to five years old. to get suffered from acute respiratory tract infection.Conclusion : There is significant correlation between ventilation space, sunlighting and density of occupants with acute respiratory tract infection suffired by children one tofiveyears old (p<0,05). On the other hand, there is no significant correlation between nutritional status tvith acute respiratory tract infection suffered by children one to five years old (p>0,05).Key Words : ARI, Risk Factor, Character Factor